1969
DOI: 10.1103/physrev.177.127
|View full text |Cite
|
Sign up to set email alerts
|

Electric Polarizabilities of the4p2Level of Potassium

Abstract: The atomic-beam technique has been used to study the Stark effect in the 4p level of potassium. The results, expressed in terms of three polarizabilities, are found to be in good agreement with the Bates and Daamgard calculation of oscillator strengths.The study of the Stark effect of atomic levels is important in that the Stark shifts are directly determined by the oscillator strengths connecting the level under study to near-lying levels of opposite parity. Hence the measurement of these shifts serves as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

1971
1971
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
3
9
0
2
Order By: Relevance
“…For Rb The scalar polarizability differences observed for rubidium and potassium are in good agreement, respectively, with the previously measured values [6,7] of 72(16)X 10 cm and 50(12)X 10 cm . Our new results are more than 1000 times more precise than these earlier values.…”
supporting
confidence: 89%
“…For Rb The scalar polarizability differences observed for rubidium and potassium are in good agreement, respectively, with the previously measured values [6,7] of 72(16)X 10 cm and 50(12)X 10 cm . Our new results are more than 1000 times more precise than these earlier values.…”
supporting
confidence: 89%
“…[42] fields of upto 2 × 10 5 (V/cm) were used to slow a molecular beam. Gould [43] used fields upto 4.6 × 10 5 (V/cm) in the measurement of atomic tensor polarizability, while Marrus et al [44] reported fields upto 10 6 (V/cm). What is perhaps most encouraging is a recent experiment for cooling molecule beams with time-dependent (adiabatic from the view point of atomic internal dynamics) fields of upto 10 7 (V/cm) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Once the equilibrium widths are found from numerically solving Eqs. (44), small amplitude oscillations can be studied by evaluating the matrix of the second order derivatives of the equivalent potential U (v x , v y , v z ) Eq. (39).…”
Section: Small Amplitude Shape Oscillationsmentioning
confidence: 99%
“….. 1 We believe that the 41 K impurity in the absorption beam is by itself negligible because of the fact that the absorption line due to component b of Fig. l(b where A is the mass number, oA the mass difference between a pair of isotopes, A the mean mass number for two isotopes, E the energy separation .…”
Section: Discussion and Resultsmentioning
confidence: 99%